2018
DOI: 10.1111/nyas.13561
|View full text |Cite
|
Sign up to set email alerts
|

IgG4‐mediated autoimmune diseases: a niche of antibody‐mediated disorders

Abstract: Immunoglobulin 4 (IgG4) is one of four human IgG subclasses and has several unique functional characteristics. It exhibits low affinity for complement and for most Fc receptors. It furthermore has generally high affinity for its antigen, with binding occurring in a monovalent fashion, as IgG4 can exchange Fab-arms with other IgG4 molecules. Because of these characteristics, IgG4 is believed to block its targets and prevent inflammation, which, depending on the setting, can have a protective or pathogenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 90 publications
(134 reference statements)
0
67
0
Order By: Relevance
“…67 These findings appeared to provide an adequate explanation for the pathogenic effect of IgG4 antibodies and suggested that the coexisting IgG1-3 antibodies were irrelevant. 68 The inhibition of LRP4 binding to MuSK by IgG4 antibodies was also shown by coimmunoprecipitation and western blotting. 64 The IgG1-3 fractions did not inhibit LRP4 binding to MuSK.…”
Section: Musk Antibodies In Vitromentioning
confidence: 91%
See 1 more Smart Citation
“…67 These findings appeared to provide an adequate explanation for the pathogenic effect of IgG4 antibodies and suggested that the coexisting IgG1-3 antibodies were irrelevant. 68 The inhibition of LRP4 binding to MuSK by IgG4 antibodies was also shown by coimmunoprecipitation and western blotting. 64 The IgG1-3 fractions did not inhibit LRP4 binding to MuSK.…”
Section: Musk Antibodies In Vitromentioning
confidence: 91%
“…Subsequent experiments by that group showed that, in a solid support assay, MuSK IgG4 antibodies inhibited the binding of LRP4 to MuSK and prevented agrin–LRP4–induced MuSK phosphorylation . These findings appeared to provide an adequate explanation for the pathogenic effect of IgG4 antibodies and suggested that the coexisting IgG1–3 antibodies were irrelevant …”
Section: Experimental Studies On Patients With Mgmentioning
confidence: 97%
“…Loss of appropriate pre-and postsynaptic alignment is also known to contribute to the NMJ dysfunction seen in MG animal models (Cole et al, 2008;Huijbers et al, 2018;Klooster et al, 2012).…”
Section: Monovalent and Bivalent Musk Antibodies Differentially Affecmentioning
confidence: 99%
“…Our data show that rendering the IgG4s bispecific and thereby functionally monovalent for the MuSK autoantigen serves as a mechanism that exacerbates the autoantibodies pathogenic potential. This may be relevant for the growing number of IgG4mediated autoimmune diseases and other disease settings where IgG4 plays a pathogenic role, such as where IgG4 blocks endogenous anti-tumor responses in melanoma patients (Daveau et al, 1977;Huijbers et al, 2018;Karagiannis et al, 2013).…”
Section: Igg4smentioning
confidence: 99%
See 1 more Smart Citation